2008
DOI: 10.1002/art.23381
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glycosaminoglycan loss on chondrocyte viability: A study on porcine cartilage explants

Abstract: Objective. Loss of glycosaminoglycan (GAG) is an early event in osteoarthritis. Recent findings showed increased cell death in arthritic cartilage and linkage with extracellular matrix degradation. The aim of this study was to analyze the direct effect of GAG loss on chondrocyte survival and cell death following mechanical injury.Methods. In full-thickness cartilage explants from porcine knee joints, GAG was depleted by digestion with chondroitinase ABC. Explants were subjected to single-impact mechanical inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 42 publications
3
37
0
2
Order By: Relevance
“…Ϫ/Ϫ mice demonstrate an increased susceptibility to apoptosis, as induced by antibody to the CD95/Fas receptor, and the SZ is more susceptible to cell death induced by mechanical stress (7). These findings suggest that chromatin factor HMGB2 may facilitate survival of SZ chondrocytes.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Ϫ/Ϫ mice demonstrate an increased susceptibility to apoptosis, as induced by antibody to the CD95/Fas receptor, and the SZ is more susceptible to cell death induced by mechanical stress (7). These findings suggest that chromatin factor HMGB2 may facilitate survival of SZ chondrocytes.…”
Section: Discussionmentioning
confidence: 83%
“…Mechanical stress has been implicated in initiating the superficial lesions (6); the SZ is more susceptible to cell death induced by mechanical stress (7), but molecular mechanisms remain to be elucidated. The SZ of articular cartilage is unique in cell morphology and extracellular matrix composition.…”
mentioning
confidence: 99%
“…3,4 A number of studies have used chondroitinase ABC (CABC) to deplete cartilage of glycosaminoglycan (GAG) and to investigate the immediate effects on both mechanical properties and biologic responses to such perturbation of the tissue. [5][6][7] CABC specifically depolymerizes chondroitin and dermatan sulfate, 8 while collagen, the collagen network arrangement, keratan sulfate, and link protein remain unaffected by the enzyme. 9,10 It has been shown that the compressive Young's modulus obtained from an indentation test decreases significantly after treatment with collagenase and CABC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the present study, we sought to determine the efficacy of TXC on chondrocyte autophagy, as a chondroprotective agent. Excessive mechanical loading of articular cartilage causes damage to chondrocytes and the ECM, and initiates a pathogenetic process that occurs due to abnormal chondrocyte activation and results in the spreading of chondrocyte death and damage to the ECM beyond the initial area that was exposed to the highest mechanical load (24,25). The understanding of the mechanisms involved in these cellular changes may provide the potential to identify targets for pharmacological interventions in order to attenuate or prevent the subsequent development of OA.…”
Section: Discussionmentioning
confidence: 99%